Colossal [videorecording (DVD)] - Vigalondo, Nacho, 1977-; Hathaway, Anne, 1982-; Sudeikis, Jason; Stevens, Dan, 1982- (Universal Pictures Home Entertainment, 2017)
Gloria is an out-of-work party girl who, after getting kicked out of her apartment by her boyfriend, is forced to leave her life in New York and move back to her hometown. When news reports surface that a giant creature is destroying Seoul, South Korea, Gloria gradually comes to the realization that she is somehow connected to this far-off phenomenon. Gloria must determine why her seemingly insignificant existence has such a colossal effect on the fate of the world.